A note on the hyperbolic-parabolic identification problem with involution and Dirichlet boundary condition - Ashyraliyev, Maksat; Ashyralyyeva, Maral A.; Ashyralyev, Allaberen (Bulletin of the Karaganda University. Mathematics Series, 2020)
In the present paper, a source identification problem for hyperbolic-parabolic equation with involution and Dirichlet condition is studied. The stability estimates for the solution of the source identification hyperbolicparabolic problem are established. The first order of accuracy stable difference scheme is constructed for the approximate solution of the problem under consideration. Numerical results are given for a simple test problem.